A commentary on Ovid's Metamorphoses, Volume 1, General Introduction and Books 1-6 - Barchiesi, Alessandro 1955-; Rosati, Gianpiero 1951- (Cambridge University Press, 2024)
Comprising fifteen books and over two hundred and fifty myths, Ovid's Metamorphoses is one of the longest extant Latin poems from the ancient world and one of the most influential works in Western culture. It is an epic on desire and transgression that became a gateway to the entire world of pagan mythology and visual imagination. This, the first complete commentary in English, covers all aspects of the text - from textual interpretation to poetics, imagination, and ideology - and will be useful as a teaching aid and an orientation for those who are interested in the text and its reception. Historically, the poem's audience includes readers interested in opera and ballet, psychology and sexuality, myth and painting, feminism and posthumanism, vegetarianism and metempsychosis (to name just a few outside the area of Classical Studies)